3D Ordered Porous Nanostructure Confers Fast Charge Transfer Rate and Reduces the Electrode Polarization in Thick Electrode. Issue 7 (5th December 2021) - Lin, Shengxuan; Wang, Yifan; Chen, Yuhang; Cai, Zihe; Xiao, Jiajia; Muhmood, Tahir; Hu, Xiaobin
Abstract: Lithium batteries with high electrode thickness always possess a poor battery property due to electrode polarization along the thickness direction. Herein, a concept that the electrode polarization can be reduced through the fabrication of 3D ordered interconnected nanostructure in the electrode is put forward. A nitrogen‐doped carbon photonic crystal (NCPC) with the ordered interconnected nanostructure is used in the electrode to prove the concept. NCPC can provide a fast charge transfer rate along the thickness direction and a uniform distribution for electrons and lithium ions, resulting in diminishing the concentration polarization and concentration gradient. When NCPC works for lithium–sulfur battery, the thick electrode achieves a fast charge transfer rate and a small voltage gap as well as the thin electrode. The 200 µm thick sulfur cathode obtains a specific capacity (87%) as high as 100 µm thick sulfur cathode. In contrast, the capacity ratio of the electrode made by the traditional coating method is only 45%. Abstract : 3D ordered interconnected nanostructure provides straight transfer routes for electrons and lithium‐ions along the electrode thickness direction, decreasing the charge transfer distance. The uniform structure also confers the even distribution of electrons and lithium‐ions. Based on the above two points, these ordered porous nanostructures can inhibit the formation of concentration gradient and reduce the electrode polarization.